Percepções de professores sobre o ensino de ciências nos anos iniciais - Ferreira, Valéria Oliveira (2020)
This research presents the Teaching of Natural Sciences in the early years of Elementary School as a scenario. This research aimed to analyze the perceptions of teachers in the early years in order to identify, in these perceptions, relevant aspects for the development of Science Education. To achieve the objectives, the study was carried out with 10 teachers who work in the initial years, two teachers from each school in a private network in Porto Alegre. The data collection took place through a semi-structured interview previously scheduled between the researcher and the interviewed teacher. The collected data, referring to the teachers' speeches, were recorded in audio and analyzed with a qualitative approach, using the Discursive Textual Analysis (DTA), described by Moraes and Galiazzi (2007), for producing new understandings about the studied speeches. The categories that emerged from the Discursive Textual Analysis process were: category 1 - considerations about the role of planning for Science Teaching in the early years under the teachers’ perception; category 2 - valuing teaching mediation in the learning process; and category 3 - recognition by teachers of the early years of the Science language in the integral education of the student. In the first category, planning stands out as dynamic, flexible and in motion, a fundamental tool to guide pedagogical actions. In the second category, the importance of teacher mediation as a central element in educational practice stands out, as well as the investigative and contextualized approach as an important assumption to intermediate the understanding of scientific knowledge and the language of Science for the understanding of reality and its purpose in everyday life, discussed in the third category. Based on the theoretical reference and analysis of the data collected, it was observed that category collaborated to understand aspects that underlie Science Education in the early years in order to contribute to the integral formation of the 21st century individual from the earliest age, also helping to understand the environment in which they live for reflective action on the different events of daily life.